The improvement effect of astaxanthin-loaded emulsions on obesity is better than that of astaxanthin in the oil phase. Issue 6 (10th March 2022) - Gao, Yuan; Yuan, Shihan; Chen, Yuze; Liu, Fang; Wei, Zihao; Cao, Wanxiu; Li, Robert W.; Xu, Jie; Xue, Changhu; Tang, Qingjuan
Abstract : AL showed better anti-obesity properties than ASTA due to their higher oral absorbability and modulating effects on the gut microbiota. Abstract : Emulsion-based delivery systems have been reported to improve the solubility, stability and bioavailability of astaxanthin. In this study, the ability of astaxanthin-loaded emulsions (AL) to ameliorate obesity induced by a high-fat and high-sucrose diet was explored, using astaxanthin in the oil phase (ASTA) as a comparison. After the administration of AL, ASTA (30 mg per kg body weight), or saline on normal or obese mice for 4 weeks, the body fat accumulation levels, hepatic lipid contents and hepatic fatty acid profiles were detected, and AL showed better anti-obesity properties than ASTA. In an acute feeding experiment, it was first observed that the astaxanthin concentration of AL was higher than that of ASTA in the blood and liver of obese mice. What's more, AL altered the microbial co-occurrence patterns in obese mice. Some gut microbial modules that were significantly correlated with obesity-related physiological parameters were identified. Overall, the improvement effect of AL on obesity is better than that of ASTA due to their higher oral absorbability and modulating effects on the gut microbiota, and we suggest AL as a more suitable astaxanthin product type for obese bodies.